DfAM: development of design rules for FFF - Djokikj, Jelena; Kandikjan, Tatjana (Elsevier BV, 2022)
The Additive Manufacturing (AM) technologies have huge advancement since their appearance in the late 90ties. The popularization of AM is due to their unique characteristics enabled by their specific working manner. The specific working manner requires new methodologies and approaches in the design process. With this paper we make contribution in that area. We are proposing a methodology for development of design rules for working with fused filament fabrication (FFF) process. Additionally we developed a set of design rules for designing and preparing for fabrication with FFF.
Keywords: design for additive manufacturing (DfAM), design rules, fused filament fabrication (FFF), design process